1984
DOI: 10.1016/0014-5793(84)80779-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activation of tissue plasminogen activator by plasma and tissue enzymes

Abstract: Tissue kallikrein and factor Xa were found to activate tissue plasminogen activator (t-PA) at a rate comparable with that of plasmin. During the activation reaction, the single-chain molecule was converted into a two-chain form. A slight t-PA activating activity was also found in plasma kallikrein. Other activated coagulation factors, factor XIIa, factor XIa, factor IXa, factor VIIa, thrombin and activated protein C had no effect on t-PA activation. t-PA was also activated by a tissue kallikrein-like enzyme th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 26 publications
3
30
0
1
Order By: Relevance
“…Furthermore, the fact that PAs act as a part of a cascade reaction implies a more complicated set of control mecahnisms for the final proteolytic effect. Recent demonstration of proenyzmes with little or no activity (3,17,27,32,51,67,68,82) suggests that mechanisms, although at present unknown, exist that control the conversion of zymogens to active enzymes in the extracellular space. Moreover, u-PA is inhibited by the abundant protease inhibitors of the human plasma, by the protease nexin, and by the recently reported more specific inhibitors (see our introductory text for references).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that PAs act as a part of a cascade reaction implies a more complicated set of control mecahnisms for the final proteolytic effect. Recent demonstration of proenyzmes with little or no activity (3,17,27,32,51,67,68,82) suggests that mechanisms, although at present unknown, exist that control the conversion of zymogens to active enzymes in the extracellular space. Moreover, u-PA is inhibited by the abundant protease inhibitors of the human plasma, by the protease nexin, and by the recently reported more specific inhibitors (see our introductory text for references).…”
Section: Discussionmentioning
confidence: 99%
“…The beads were then washed three times with PBST and stored for up to 2 wk at 4VC without a detectable loss of bound protein. Using 11-fibrinogen, 4.0 X 101 molecules of fibrinogen bound per 3-,um-diam bead with a 95% coupling efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Human tissue plasminogen activator (t-PA)' is an essential enzymatic component in the constellation of proteins that that tct-PA is considerably more active than sct-PA (3)(4)(5), and these investigators have suggested that any measured activity in preparations of sct-PA represent contamination by small amounts of the two-chain form. Other investigators have reported that sct-PA does have significant intrinsic enzymatic activity (6-1 1).…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary function of PL is to remove intravascularly formed thrombin by the degradation of Fn, PL has many other actions, such as the degradation of adhesive macromolecules, 10-13) the activation of growth factors, 14,15) coagulation factor modification, 16,17) the activation of t-PA 18) and u-PA, 19) and so on. As a result, PL might function in pathologic phenomena, such as inflammation 20) and tumor cells growth and metastasis.…”
Section: )mentioning
confidence: 99%
“…Plasma kallikrein (PK) (EC 3.4.21.34), which is one component of the contact system, 7) probably mediates the activation of prourokinase and accelerates the PL formation, 8) while PK was reported to activate the contact phase of coagulation. 9) Although the primary function of PL is to remove intravascularly formed thrombin by the degradation of Fn, PL has many other actions, such as the degradation of adhesive macromolecules, [10][11][12][13] the activation of growth factors, 14,15) coagulation factor modification, 16,17) the activation of t-PA 18) and u-PA, 19) and so on. As a result, PL might function in pathologic phenomena, such as inflammation 20) and tumor cells growth and metastasis.…”
mentioning
confidence: 99%